Between East and South spaces of interaction in the globalizing economy of the Cold War - Calori, Anna; Hartmetz, Anne-Kristin; Kocsev, Bence; Mark, James 1972-; Zofka, Jan 1975- (Dialectics of the global, 2019)
Intro -- Dialectics of the Global -- Preface -- Contents -- 1.` Alternative Globalization? Spaces of Economic Interaction between the "Socialist Camp" and the "Global South" -- 2. The "Grapes of Cooperation"? Bulgarian and East German Plans to Build a Syrian Cement Industry from Scratch -- 3. The Soviet Union, the CMEA, and the Nationalization of the Iraq Petroleum Company, 1967-1979 -- 4. Diverging Visions in Revolutionary Spaces: East German Advisers and Revolution from above in Zanzibar, 1964-1970 -- 5. The GDR, SWAPO, and Namibia: Economic and Other Interactions in the 1970s and 1980s -- 6. Agents of Decolonization? Romanian Activities in Mozambique's Oil and Healthcare Sectors, 1976-1984 -- 7. Czechoslovak Economic Interests in Angola in the 1970s and 1980s -- 8. Bartering Within and Outside the CMEA: The GDR's Import of Cuban Fruits and Ethiopian Coffee -- 9. The End of Alternative Spaces of Globalization? Transformations from the 1980s to the 2010s -- List of Contributors -- Index.